Microelectrode arrays for electroanalytical sensing : Comparison of electroplating and electron-beam metallisation. - Delcourt Lancon, A; Kataky, R; Wood, D; Gallant, A.J. (Electrochemistry Communications, 2011)
This paper demonstrates the differences in electrochemical response obtained by two distinct methods of gold microelectrode array fabrication. An array of 306 gold recessed microelectrodes (45 μm in diameter) was fabricated using lithography, metallisation and oxygen plasma treatment processes. The microelectrodes characterised using cyclic voltammetry and AFM showed a marked change in surface roughness from 0.88 nm to 9.76 nm by using electroplating metallisation. This increase resulted in a substantial improvement in the MEA activity while maintaining the behaviour of the microelectrode array; a finding that indicates the cheaper electroplating technique is preferable for producing sensitive and reproducible MEAs.
Keywords: Microelectrode; Array; Metallisation; Roughness; Atomic Force Microscopy.